1977
DOI: 10.1007/bf00571277
|View full text |Cite
|
Sign up to set email alerts
|

Replication of plasmid pSC101 inEscherichia coli K12: Requirement fordnaA function

Abstract: Replication of pSC101 was analyzed by using DNA-DNA hybridization and alkaline sucrose gradient centrifugation. Mutants of the dnaA gene were tested for their capacity to replicate pSC101 DNA at a non-permissive temperature. Only a small amount of radioactive precursor was incorporated into pSC101 DNA in dnaA mutants at 42 degrees C whereas active incorporation into plasmid DNA took place in dnaA+ strain under the same conditions. The effect of the dnaA mutation was grater on plasmid DNA synthesis than on host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 15 publications
8
89
0
Order By: Relevance
“…The qPCR method yielded a copy number of 16.5 plasmids/chromosome for pBR322, consistent with a range of 15-20 plasmids per chromosome (Lee et al, 2006;LinChao and Bremer, 1986). In addition, pWSK29 was found to have a copy number of 6.7 plasmids/chromosome, closely matching previous measurements for pSC101 of ∼6 plasmids/ chromosome (Cabello et al, 1976;Hasunuma and Sekiguchi, 1977). Measurements of the high copy number mutants showed the repAE93K mutation resulted in a copy number of 27 plasmids/chromosome.…”
Section: Plasmid Copy Number Determinationsupporting
confidence: 84%
See 1 more Smart Citation
“…The qPCR method yielded a copy number of 16.5 plasmids/chromosome for pBR322, consistent with a range of 15-20 plasmids per chromosome (Lee et al, 2006;LinChao and Bremer, 1986). In addition, pWSK29 was found to have a copy number of 6.7 plasmids/chromosome, closely matching previous measurements for pSC101 of ∼6 plasmids/ chromosome (Cabello et al, 1976;Hasunuma and Sekiguchi, 1977). Measurements of the high copy number mutants showed the repAE93K mutation resulted in a copy number of 27 plasmids/chromosome.…”
Section: Plasmid Copy Number Determinationsupporting
confidence: 84%
“…pSC101-derivative plasmids are also stably maintained owing to the presence of the par locus (Tucker et al, 1984). pSC101-derivative plasmids replicate at a relatively low copy number (<8 copies/cell) (Cabello et al, 1976;Hasunuma and Sekiguchi, 1977) and numerous cloning vectors based on this replicon have been reported (Hashimoto-Gotoh et al, 2000;Hasnain and Thomas, 1986;Hoang et al, 1999;Lerner and Inouye, 1990;Phillips, 1999;Stoker et al, 1982;Takeshita et al, 1987;Wang and Kushner, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…1). Previously we had observed that expression of umuDC from a high-copynumber plasmid (pBR322) would partially suppress the nonmutability of the groE strains (6 suppression because of increased gene dosage, we assayed UV mutagenesis in strains in which the umuDC or umuD'C genes were expressed from a relatively low-copy-number plasmid (pSC101, with approximately 8 copies per chromosome) (14). Under these conditions, the nonmutability phenotype of groEL100 and groES30 derivatives of AB1157 is only slightly suppressed by a plasmid encoding umuDC, pSE115 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that DnaA protein can participate in the initiation event of the oriVaSFlOlo-dnaA box in pYTAI, especially in the priming reaction which may be directed by the inserted dnaA box. It has been reported that plasmid pSCIO1, the replication origin of which has a dnaA box, reduces its copy number when it is in a dnaA temperature-sensitive mutant even at the permissive temperature [25]. This inability of replication of the pYTA1 in the dnaA46 mutant seems to be similar to the case of pSC101.…”
Section: Discussionmentioning
confidence: 81%